2012
DOI: 10.1111/j.1349-7006.2012.02370.x
|View full text |Cite
|
Sign up to set email alerts
|

SYTSSX breakpoint peptide vaccines in patients with synovial sarcoma: A study from the Japanese Musculoskeletal Oncology Group

Abstract: In the present study, we evaluated the safety and effectiveness of SYT-SSX-derived peptide vaccines in patients with advanced synovial sarcoma. A 9-mer peptide spanning the SYT-SSX fusion region (B peptide) and its HLA-A*2402 anchor substitute (K9I) were synthesized. In Protocols A1 and A2, vaccines with peptide alone were administered subcutaneously six times at 14-day intervals. The B peptide was used in Protocol A1, whereas the K9I peptide was used in Protocol A2. In Protocols B1 and B2, the peptide was mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 43 publications
2
62
0
Order By: Relevance
“…STS often are divided biologically into 2 categories: genetically “simple” and “complex” tumors. The simple tumors tend to have specific, reliably identifiable oncogenic alterations (such as translocations) and a limited number of mutated neoantigens 13, 14. Synovial sarcoma (SS) and myxoid/round cell liposarcoma (MRCL) both are translocation‐driven malignancies and often express high levels of self‐antigens, notably NY‐ESO‐1,15, 16 which has been targeted with promising signals of efficacy 6, 17…”
Section: Introductionmentioning
confidence: 99%
“…STS often are divided biologically into 2 categories: genetically “simple” and “complex” tumors. The simple tumors tend to have specific, reliably identifiable oncogenic alterations (such as translocations) and a limited number of mutated neoantigens 13, 14. Synovial sarcoma (SS) and myxoid/round cell liposarcoma (MRCL) both are translocation‐driven malignancies and often express high levels of self‐antigens, notably NY‐ESO‐1,15, 16 which has been targeted with promising signals of efficacy 6, 17…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that SYT-SSX fusion peptides are recognized by HLA-A24+ synovial sarcoma patients and result in tumor specific cytotoxic responses [17,22]. Further, a pilot trial of a wild-type SYT-SSX derived peptide vaccine confirmed its safety and its ability to evoke in vivo i mmunological responses [23].…”
Section: Tumor-associated Antigens In Synovial Sarcomamentioning
confidence: 96%
“…Recently, the Japanese Musculoskeletal Oncology Group reported their phase I experience using vaccination with a 9-mer SYT-SSX derived peptide with and without systemic interferon-alpha for patients with metastatic synovial sarcoma. 34 The vaccines were well tolerated and antigen-specific cytotoxic T cell responses were seen in vitro. Disease stabilization was observed in 6 out of 12 (50%) of patients who had received vaccine with interferon versus 1 out of 9 (11%) patients who had received the vaccine alone.…”
Section: Cancer Vaccinesmentioning
confidence: 99%